MANAJEMEN PENDIDIKAN STRATEGIS DALAM MENGEMBANGKAN MADRASAH DINIYAH TAKMILIYAH AWWALIYAH NURUL MANNAN DESA BANJAR BARAT KECAMATAN GAPURA KABUPATEN SUMENEP - Suwantoro Suwantoro; Rusdiana Navlia (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
Education management, especially strategic management will have a positive impact in the process of developing better and more perfect educational institutions. There are three issues that are the main subject of this study, namely: First: How is the head of the madrasa in developing Diniyah Takmiliyah Awwaliyah Nurul Mannan Madrasah Banjar Barat Village, Gapura District, Sumenep Regency? Second: How is the management of strategic education implemented in the Diniyah Takmiliyah Awwaliyah Nurul Mannan Madrasah, Banjar Barat Village, Gapura District, Sumenep District? Third: What are the supporting and inhibiting factors for the implementation of strategic education management in developing Diniyah Takmiliyah Awwaliyah Nurul Mannan Madrasah Banjar Barat Village, Gapura District, Sumenep Regency? This study uses a qualitative approach in the form of descriptive data sources obtained through interviews, observation, and documentation. The informants were the Head of Madrasah, The Ustazz, and some of the students of the Diniyah Takmiliyah Awwaliyah Nurul Mannan Madrasah Banjar Barat Village, Gapura District, Sumenep Regency. Analysis of the data used is descriptive analysis, in which to support and strengthen the findings of the data validity check through research persistence, and triangulation.